Pengaruh Motivasi, Kompensasi dan Kepemimpinan terhadap Disiplin Pegawai di Sektor Penanggulangan Kebakaran dan Penyelamatan Kecamatan Jatinegara - Ahmad Faisal; Euis Komalawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
Work discipline is an attitude of awareness and willingness of a person to comply with all applicable regulations and norms in an organization. Work discipline is a very important attitude in the world of work and is an individual’s awareness and commitment to the organization. This study discusses and analyzes the effect of motivation, compensation and leadership on employee discipline in the Fire Fighting and Rescue Sector of Jatinegara District. This study used a quantitative method applying a questionnaire distribution technique to 43 respondents, being the entire population. Data analysis was carried out by using multiple regression running a SPSS software. The results of the study indicate that motivation had a positive and significant effect on employee discipline, with a determination coefficient (R Squrare) of 0,234 or 23,4%; the compensation had a positive and significant effect on employee discipline with a determination coefficient (R Square) of 0,351 or 35,1%; and leadership had a positive and significant effect on employee discipline with a determination coefficient (R Square) of 0,327 or 32,7%. Independent variables of motivation, compensation and leadership were simultaneously tested by using the F test proving that they had a positive and significant effect with an Fcount value of 18,602 on employee discipline and a determination coefficient (R Square) of 0,589 or 58,9%.